PENYULUHAN PERUBAHAN STRUKTUR FISIK DAN PEMERIKSAAN POSTURAL PADA LANSIA DI BANJAR KESIAN, DESA LEBIH GIANYAR - Karunia Saraswati, Ni Luh Putu Gita; Nugraha, Made Hendra Satria; Putra, I Putu Yudi Pramana; Thanaya, Sayu Aryantari Putri (Buletin Udayana Mengabdi, 2020)
The number of elderly in Banjar Kesian, Desa Lebih, Gianyar has increased from year to year. Most of the elderly in Banjar Kesian, Desa Lebih are productive and still carry out their daily activities such as community activities, farming, etc. Thus, there should be an effort to increase the awareness of elderly on how to maintain their well-being during performing their daily activities, for example by providing counseling or education about problems that can occur due to the physical changes experienced by the elderly and doing a form of screening or examination related to the physical changes in the elderly, for example postural examination. Community service was provided to the elderly in Banjar Kesian, Desa Lebih, Gianyar. There were 42 elderly people (14 men and 28 women) who participated in this service. The results of the analysis of respondents showed there were 28 people aged 60-69 years, 8 people aged 70-79, and 6 people aged 80-89 years.